The Influences of Impulsivity and Education Levels on Severity of Alcohol Dependence - Liu, Ziqi; Luo, Ruyan; Fu, Rao; Yuan, Chenxin; Xu, Xueming; Zhou, Dongsheng; Zhao, Min; Yuan, Ti-Fei; Du, Jiang (Frontiers in Psychiatry, 2020)
Background: Impulsivity contributes to the severity of alcohol use disorders (AUD). The association is affected by expectation towards alcohol use, emotional regulation and self-control. Here we investigated the influences of self-reported impulsivity and levels of education on severity of alcohol dependence. Method: We retrospectively analyzed the basic demographic information, alcohol consumption state, education years, depression and anxiety state, Alcohol use disorder Identification Test (AUDIT) and Barrett Impulsivity Scales (BIS) from a group of 66 AUD patients. Result: Impulsivity significantly predicted alcohol dependence severity (R2 = 0.069, F = 4.724, p = 0.034). In addition, education years served as a moderator in the relationship between impulsivity and alcohol dependence severity (ΔR2 = 0.059, F = 4.414, p = 0.040). Conclusion: Self-reported impulsivity affects the severity of alcohol dependence, which might be different in patients with different education levels.